Esterification of free fatty acids in used cooking oil using ion-exchange resins as catalysts: An efficient pretreatment method for biodiesel feedstock - Sumaiya, Zainal Abidin; F. Haigh, Kathleen; Saha, Basudeb (American Chemical Society (ACS Publications), 2012)
The esterification of used cooking oil (UCO) with methanol was studied using different types of ion-exchange resins, that is, Purolite D5081, Purolite D5082, and Amberlyst 36. Several catalyst characterization analyses (elemental analysis, surface area measurement, particle size distribution analysis, scanning electron microscopy analysis, true density measurement, and acid capacity analysis) have been conducted in the screening stage. Of all of the catalysts investigated, Purolite D5081 resin showed the best catalytic performance and was selected for further experimental studies. The esterification process was carried out in a jacketed stirred batch reactor for 8 h. Elimination of mass transfer resistances and the effect of catalyst loading (0.5–1.5% w/w), reaction temperature (50–65 °C), and methanol to UCO feed mole ratio (4:1–12:1) on the conversion of FFAs were investigated. The highest FFAs conversion was found to be 92%, at a catalyst loading of 1.25% w/w, 60 °C reaction temperature, 6:1 methanol to UCO molar ratio, and stirring speed of 475 rpm. During the reusability study, the conversion of catalyst dropped by 8–10% after each reutilization cycle. Several experiments have been conducted through the homogeneous contribution study, and the results confirmed that both resin pore blockage and sulfur leaching are dominant factors that decrease the catalytic performance of Purolite D5081 ion-exchange resin.